Effectiveness of corona lockdowns: Homburg's flawed analysis - Stefan Felder; Bernt-Peter Robra (University of Basel, Center of Business and Economics (WWZ), 2020)
This is a comment on Homburg (2020) who claimed that lockdowns were superfluous and ineffective. We demonstrate major flaws: Homburg's data base is not suitable to support his claim and his econometric approach does not allow for an analysis of a lockdown's incremental effect.
Keywords: I18; 330; Corona; SARS-CoV-2; Covid-19; Lockdown